Evaluasi Efektivitas dan Keamanan Penggunaan Obat Anestesi Umum di RS PKU Muhammadiyah Yogyakarta - Inayati, Istiqoma Dewi Kurniawati Zullies Ikawati (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
Anesthesia is given to more than 75 million surgical patients annually, wordwide. An ideal anesthetic drug would induce anesthesia smoothly and rapidly while allowing for prompt recovery after its administration is discontinued. The drug would also prossess a wide margin of safety and be devoid of adverse effects. The objective of the study was to get an overview on use of general anesthesia at PKU Muhammadiyah hospital, Yogyakarta which included aspects of dose induction relevance, effectiveness of general anesthesia based on onset dan duration recovery and safety based on cardiovascular and respiratory side effects which happened due to induction anesthesia.The study used descriptive case series design carried out prospectively. Data were obtained from observation of elective surgery patient in Instalasi Bedah Sentral at PKU Muhammadiyah hospital, Yogyakarta. Sample were collected by concecutive sampling methods on Maret-Juni 2010. Onset, duration recovery were monitored after induction anesthesia. Systolic and diastolic blood pressure, heart rate, saturation were monitored 0 minute before induction and 5 minute after induction anesthesia.From 84 patient, as many as 72,62%Â  were relevant dose with induction and 27,38% were irrelevant dose. Effectivity anesthesia based on onset was 100% effective Recovery from isoflurane was 4-11 minute faster than with sevoflurane and 1-4 minute faster than hallotane. Cardiovascular side effect was not significant between relevant and irrelevant dose Induction. No respiratory side effect was found.